Legislation for smoke-free workplaces and health of bar workers in Ireland: before and after study - Allwright, Shane (BMJ Publishing Group Ltd., 2005)
Objectives To compare exposure to secondhand smoke and respiratory health in bar staff in the Republic of Ireland and Northern Ireland before and after the introduction of legislation for smoke-free workplaces in the Republic. Design Comparisons before and after the legislation in intervention and control regions. Setting Public houses in three areas in the Republic (intervention) and one area in Northern Ireland (control). Participants 329 bar staff enrolled in baseline survey; 249 (76%) followed up one year later. Of these, 158 were non-smokers both at baseline and follow-up. Main outcome measures Salivary cotinine concentration, self reported exposure to secondhand smoke, and respiratory and sensory irritation symptoms. Results In bar staff in the Republic who did not themselves smoke, salivary cotinine concentrations dropped by 80% after the smoke-free law (from median 29.0 nmol/l (95% confidence interval 18.2 to 43.2 nmol/l)) to 5.1 nmol/l (2.8 to 13.1 nmol/l) in contrast with a 20% decline in Northern Ireland over the same period (from median 25.3 nmol/l (10.4 to 59.2 nmol/l) to 20.4 nmol/l (13.2 to 33.8 nmol/l)). Changes in self reported exposure to secondhand smoke were consistent with the changes in cotinine concentrations. Reporting any respiratory symptom declined significantly in the Republic (down 16.7%, -26.1% to -7.3%) but not in Northern Ireland (0% difference, -32.7% to 32.7%). After adjustment for confounding, respiratory symptoms declined significantly more in the Republic than in Northern Ireland and the decline in cotinine concentration was twice as great. Conclusion The smoke-free law in the Republic of Ireland protects non-smoking bar workers from exposure to secondhand smoke.